DISCOUNT AND ACCOUNTING PRACTICES COMMISSION (Third Sector Social Economic Review, 2015)
The similarities between accounting practices in terms of discounts and commissions will be presented with the help of examples of accounting records with this study. Performed in the application of the discount for lack of commercial life, including the KDV base; to commercial usage, have the appropriate amount of goods and services, organized in relation to the original sales invoice or similar document, also on show, will be presented in terms of thelegislation should be implemented as from cost reductions. Then the turnover of the year when the premium end of the vesting billed as a requirement of the accrual basis of accounting, even if held next year should be declared as income in the year that these primary entitlement, the tax base for the calculation of the discount of the transactions with related parties, especially the issue of whether itshould be determined according to commercial usage, in accordance with the arm's length principle, if the turnover of firms that get lower premiums for commercial gain is an individual taxpayer's income, institutions of whether the taxpayer's corporate income should be taxed as income will be dealt with separately.
Keywords: Accounting; Discount; premium revenue; Commission; Tax